E-government in Poland – selected issues - POPIOŁEK, MALWINA (Journal of Education Culture and Society, 2020)
Nowadays, the development of e-government is one of the biggest challenges for many countries around the world. Levels of e-government are very important indicators of infor-mation society structure advancement in the country. Development of e-government often faces many different obstacles. This article focuses on issues relating to some problems associated with the development of e-government in Poland.